Clementine mandarin orange peel and pulp, grape pomace and seed extracts as potential preservatives for beef patties - Bambeni, Thandikhaya (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScAgric)--Stellenbosch University, 2021.